Tutorial: Finding the Correct Permutation for a Transformed Sequence

In this tutorial, we will learn how to compute a permutation that transforms one sequence into another after applying a sequence of permutations. Specifically, we will use the following problem:
在这里插入图片描述

Problem Statement

We are given:

  1. An original sequence S = ['A', 'B', 'C', 'D', 'E', 'F'].
  2. First permutation (P1): A permutation applied to S to get S'. For example:
    P 1 = [ 5 , 2 , 3 , 4 , 0 , 1 ] P1 = [5, 2, 3, 4, 0, 1] P1=[5,2,3,4,0,1]
    Applying P1 to S gives S':
    S ′ = [ F , C , D , E , A , B ] S' = [F, C, D, E, A, B] S=[F,C,D,E,A,B]
  3. Second permutation (P2): A permutation applied to the original sequence S to get a new sequence S''. For example:
    P 2 = [ 2 , 3 , 4 , 1 , 0 , 5 ] P2 = [2, 3, 4, 1, 0, 5] P2=[2,3,4,1,0,5]
    Applying P2 to S gives S'':
    S ′ ′ = [ C , D , E , B , A , F ] S'' = [C, D, E, B, A, F] S′′=[C,D,E,B,A,F]

Our goal is to find a permutation P such that applying P to S' (i.e., the result of applying P1 to S) gives S''.

Mathematical Representation

We want to find P such that:
S ′ ′ = P ( S ′ ) = P ( P 1 ( S ) ) S'' = P(S') = P(P1(S)) S′′=P(S)=P(P1(S))
where S' is the result of applying P1 to S, and S'' is the result of applying P2 to S.


Step-by-Step Solution

Step 1: Compute the Inverse of Permutation P1

The first thing we need to do is compute the inverse of P1, denoted as P1^{-1}. The inverse of a permutation P is the permutati

评论
添加红包

请填写红包祝福语或标题

红包个数最小为10个

红包金额最低5元

当前余额3.43前往充值 >
需支付:10.00
成就一亿技术人!
领取后你会自动成为博主和红包主的粉丝 规则
hope_wisdom
发出的红包
实付
使用余额支付
点击重新获取
扫码支付
钱包余额 0

抵扣说明:

1.余额是钱包充值的虚拟货币,按照1:1的比例进行支付金额的抵扣。
2.余额无法直接购买下载,可以购买VIP、付费专栏及课程。

余额充值